#TITLE_ALTERNATIVE# - Adi Wahjono (NIM 232 98 207), Soerachmad
Abstract : Since DS CDMA (Direct Sequence Code Multiple Access) capacity is interference limited, power approach method is required to determine both radius and cell capacity. The optimum utilization and performance can be achieved using CAC (Call Admission Control) that control number of user directly. CAC should guarantee GoS (Grade of Service) i.e. blocking probability and communication quality due to communication loss. Mobile cellular system has a specific traffic characteristic due to handoff. Handoff rate and handoff calling arrival rate (due to handoff) both determine the offered traffic, therefore both of them will influence the system performance. Handoff rate is function of cell radius and MS (Mobile Station) mobility. This thesis focuses on the MS mobility effect to the traffic provided in multi cell service area and guard channel allocation. Analytic and simulation are used as research method. Determination of cell capacity is performed using power approach method. Based on user density, traffic data and the capacity, cell radius can be obtained. Then the influences of MS mobility and guard channel allocation on the system performance are examined. The analysis and simulation results indicate that supported traffic decrease as MS mobility increase. In a system using guard channel allocation, the results indicate that one guard channel allocation is optimal in macro cell CAC case.